Student factor inï¬‚ uencing Indonesian student reading literacy based on PIRLS data 2011 - Ratri, Safitri Yosita (JOURNAL OF EDUCATION, 2015)
The study was aimed at (1) examining how student factors (home parental involvement, students' perceptions of reading, reading outside school, and information and communications technology [ICT] use) inï¬‚ uenced readingliteracy, and (2) investigating how the factor interacts with reading aspects (reading experience, process and comprehension, and reading attitudes and behaviours). The subjects was quantitative research and applied Rasch and hierarchical linear modelling (HLM) analyses. The subjects were 4779 Primary-School students nested within 158 schools sampled using a random sampling technique. The study used Progress in International Reading Literacy (PIRLS) 2011 data that was categorized as secondary data. Findings of the study revealed that (1) there were signiï¬ cant relationships between a number of student factors and reading literacy in both 2011 and (2) there were identiï¬ able signiï¬ cant correlations between reading literacy and home parental involvement, students' perceptions of reading, reading outside school, and information and communications technology [ICT] in 2011